Congenital malformations in brachycephalic dogs: A retrospective study - Estevam, Marina Vilela; Beretta, Samara; Smargiassi, Nathalia F.; Apparício, Maricy; Toniollo, Gilson Helio; Pereira, Gener T. (Frontiers in Veterinary Science, 2022)
The popularity of brachycephalic dogs has increased in recent years due to their docile temperament and peculiar features. The historical inbreeding and consequent lack of genetic diversity involved in the development of these breeds led to an increase in the manifestation of deleterious genes that may lead to malformations. In addition, there are serious health issues intrinsic to the conformation, mainly attributed to these extreme characteristics. Therefore, this retrospective study aimed to observe the frequency of malformations in brachycephalic dogs compared to the pure and mixed breeds (MB). The medical records of pregnant bitches admitted at the Service of Obstetrics and Animal Reproduction (SORA) from January 2017 to December 2021 were retrieved from the Hospital's computer system and analyzed one by one. Seven hundred sixty-eight neonates born from 168 litters were included in this study. Of these litters, 72.6% (122/168) were brachycephalic. Malformations were found in 52 puppies, with an incidence of 6.77% (52/768). Of the 32 litters that produced malformed puppies, 28 were brachycephalic (87.5%). In total, 23 types of malformations were registered, the most common being cleft palate (1.30%) and anasarca (1.17%). Ten of the puppies (10/52; 19.23%) presented two or more associated malformations. Bitches above 7 years were more prone to present malformed puppies in their litters. Brachycephalic breeds were 3.03 times more likely to present malformed neonates when compared to other breeds; the odds ratio increased to 5.07 when modern brachycephalic was compared to ancestral brachycephalic. Regarding the mode of delivery, elective cesarean sections accounted for 66.6% of births while 19.64% were eutocic vaginal deliveries, and 13.69% were dystocic. The presence of malformed puppies in a litter causes suffering for the owner and for the puppy itself, therefore, the veterinarian plays a key role in this scenario. Knowledge about congenital abnormalities, their causes, diagnosis, and approach is essential to reduce the incidence of malformations and improve the quality of life of these animals.